PERANCANGAN PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) PEMBASMI SERANGGA PADA TANAMAN BAWANG MERAH DI KABUPATEN BREBES - Sudarmono Sudarmono; Joko Waluyo; Wahyu Wilopo (Journal of Appropriate Technology for Community Services, 2020)
Indonesia is located on the equator, so Indonesia has a large source of solar energy with an average solar radiation intensity of about 4.8 kWh/m2 per day throughout the region.  Solar cells are increasingly popular with the community because of their unlimited energy sources and environmentally friendly.  See the current number of fossils used as power plants continue to decrease, if left continuously, then this energy source will be depleted. Therefore scientists are vying for ways to increase renewable energy efficiency as a source of electrical energy generation One of them is solar panels.  Brebes County is located between 6044 '-7021 ' south latitude and 108041 '-109011 ' east longitude. The cultivation of red onion plants is an flagship product with a production of 272,598.8 (Ton) in the year 2017. Farmers in eradicating insect pests that do not damage the environment is to use lamps at night as an insect trap media or planthopper. Alternative sources of electrical energy to light the lamp from solar energy by utilizing the solar panels will store the electrical energy on the battery of the day and at night can be used to light the lights. The research aims to determine the feasibility of a PLTS in the red onion farm, this method is focused on the first approach of estimation of electrical needs through secondary data, LED lights on for 12 hours of 1 watt lamp load with 3 watt PV module, 6 Volt Use 3.7 volt lithium battery with 3.4 Ah old capacity charging 3.46 hours and long the illumination of the Matahri on a 4-hour PV. From these results, the PLTS are said to be worthy of alternative energy.